Desenvolvimento de baixo impacto aplicado ao Campus Samambaia da Universidade Federal de Goiás - Silva, Gerani Félix do Nascimento (2015)
Conventional urban drainage, defined as a system based on rapid flow of rainwater, has been proven unsustainable. Due to increase in waterproof surfaces resulting from urban sprawl, repeated floods and flooding have been occurring, especially in more densely populated areas. In order to restore the hydrological functions of the place, the development of low impact in urban water management, in this study called low impact development (LID), aims at achieving efficiency in the protection of natural resources and meet environmental regulations in urban planning. To apply LID to Campus Samambaia, of the Universidade Federal de Goiás (UFG), since the initial urban planning and also in areas previously consolidated, compensatory techniques in urban drainage were studied based on the concept of LID. This campus was chosen as a case study because of the great densification that has been taking place there, due to the large injection of funds from the Programa de Apoio a Planos de Reestruturação e Expansão das Universidades Federais (Reuni) in the country, from 2008 to 2013, with increased impervious surfaces, reaching 45.5% of its area. To perform this study, a broad literature review on the topic, field visits, and a case study were carried out. This research sought to initially understand the relationship between urban planning and stormwater drainage. The documentary research revealed the grounds of the laws and regulations governing urban planning, drainage within the sanitation context, as well as the master plans of federal institutions of higher education (IFES) in an interface with urban stormwater drainage. Furthermore, based on the review of guides, technical manuals, articles, theses, and dissertations on the subject, the operation of compensatory techniques was detailed, subject to the limitations regarding environmental, sanitary, landscape, and technical aspects. Field visits were made to the Campus Samambaia and a field visit to the Campus São Carlos, of the Universidade Federal de São Carlos (UFSCar), in its experimental watershed, where several compensatory techniques are implemented in full scale, as a result of research trials. After confirming the feasibility of using structural and non-structural compensatory techniques at the Campus Samambaia, at the end of this study proposal guidelines were systematized for implementation in two scenarios, with 45.5% and 85.5% of impervious surfaces, the latter representing the limit allowed by the master plan of Goiânia. These recommendations were intended as a reference to the actions of both the physical expansion of UFG and future studies and similar applications.